DNA Double-Strand Breaks Activate ATM Independent of Mitochondrial Dysfunction in A549 Cells - Kalifa, Lidza (2014)
Excessive nuclear or mitochondrial DNA damage can lead to mitochondrial dysfunction, decreased energy production, and increased generation of reactive oxygen species (ROS). Although numerous cell signaling pathways are activated when cells are injured, the ataxia telangiectasia mutant (ATM) protein has emerged as a major regulator of the response to both mitochondrial dysfunction and nuclear DNA double-strand breaks (DSBs). Since mitochondrial dysfunction is often a response to excessive DNA damage, it has been difficult to determine whether nuclear and/or mitochondrial DNA DSBs activate ATM independent of mitochondrial dysfunction. In this study, mitochondrial and nuclear DNA DSBs were generated in A549 human lung adenocarcinoma cell line by infecting with retroviruses expressing the restriction endonuclease PstI fused to a mitochondrial (MTS) or nuclear (NTS) targeting sequence and a hemagglutinin antigen epitope tag (HA). Expression of MTS-PstI-HA or NTS-PstI-HA activated the DNA damage response defined by phosphorylation of ATM, the tumor suppressor protein p53 (TP53), KRAB-associated protein (KAP)-1, and structural maintenance of chromosomes (SMC)-1. Phosphorylated ATM and SMC1 were detected in nuclear fractions whereas phosphorylated TP53 and KAP1 were detected in both mitochondrial and nuclear fractions. PstI also enhanced expression of the cyclin-dependent kinase inhibitor p21 and inhibited cell growth. This response to DNA damage occurred in the absence of detectable mitochondrial dysfunction and excess production of ROS. These findings reveal DNA DSBs are sufficient to activate ATM independent of mitochondrial dysfunction and suggest that the activated form of ATM and some of its substrates are restricted to the nuclear compartment, regardless of the site of DNA damage.